Comparison of clinical features of acute lower respiratory tract infections in infants with RSV/HRV infection, and incidences of subsequent wheezing or asthma in childhood - Ding, Qin; Xu, Lili; Zhu, Yun; Xu, Baoping; Chen, Xiangpeng; Duan, Yali; Xie, Zhengde; Shen, Kunling (BMC infectious diseases, 2020)
To compare the clinical characteristics of acute lower respiratory tract infections (ALRTIs) caused by respiratory syncytial virus (RSV) and human rhinovirus (HRV) and to explore the relationship between the development of recurrent wheezing/asthma and RSV/ HRV infections in infancy. Retrospective study was conducted to compare the clinical characteristics of acute lower respiratory tract infections (ALRTIs). Hospitalized patients with ALRTIs from March 2007 to December 2016 were screened. Single RSV cases (s-RSV), single HRV cases (s-HRV), and cases who had co-infection with the two viruses were enrolled. Follow-up was performed to determine whether either specific respiratory virus infection was related to subsequent development of recurrent wheezing/asthma. The s-RSV children were the youngest (P = 0.021), they experienced the most serious condition (P < 0.001) and respiratory failure (P < 0.001), they also required highest demand of oxygen therapy (P < 0.001). And in s-RSV group, the incidence of development of recurrent wheezing was significantly higher in subgroup with the family history of wheezing than that without (P < 0.001). The s-RSV cases suffered from the worst severity of illness, respiratory failure and required highest demand of oxygen therapy. Recurrent wheezing was more common in s-RSV group with family history of wheezing than those without.